Использование пьезоприводов в средствах автоматизации операции производственного контроля электронных компонентов - Жарикова, И. В.; Михайлов, А. А. (ХТУРЭ, 2012)
In this article the advantages, disadvantages and applications of piezoactuators are considered. The possibility of piezoactuators using for manufacturing testing process of electronic components is researched.
Keywords: пьезопривод; производственный контроль; электронные компоненты; средства автоматизации